Studies in symbolic interaction. Vol. 53 - Denzin, Norman K. (Studies in symbolic interaction., 2021)
Volume 53 of Studies in Symbolic Interaction is divided into three parts, providing contemporary readings of social situations. Part 1 includes three pathbreaking essays interpreting translational science. This is the study of the general scientific, medical and operational principles that turn observations into interventions, helping to improve patients' lives. Part 2 consists of five essays, including an analysis of the 'Phantasmal in Qualitative Research' and 'Miami's Sea-level Rise Committee'. Part 3, Norman K. Denzin and Studies in Symbolic Interaction, includes essays by Shing-Ling Sarina Chen, Michael Katovich and Joe Kotarba.